Before Big Blue : Sports at the University of Kentucky, 1880-1940 - Stanley, Gregory Kent, 1958- (Book collections on Project MUSE., 2015)
In the heart of the Bluegrass, basketball is king of collegiate athletics. But it wasn't always so. Before Big Blue chronicles the early history of organized sports at the University of Kentucky, from the tenuous beginnings under student leadership, through the early scandals, financial instability, and clashes with administration, to the Purge of 1938 that paved the way for basketball's ascendancy. Once upon a time in Lexington, football ruled the athletic department. In the 1890s and 1900s the most intense competition was with crosstown rival Transylvania University. The annual Thanksgiving.